Principals' Instructional Leadership and Support Needs in Prekindergarten and Kindergarten: A Case Study in Texas - Christopher P. Brown; Pedro Reyes; Lauren C. McKenzie; David E. DeMatthews; Sarah L. Woulfin (SAGE Publishing, 2024)
In states that fund public prekindergarten and kindergarten in elementary schools, principals are central to ensuring these programs support children's learning and development. Yet few studies explore how principals position these programs within their instructional leadership and what they perceive should be done by district leaders to support their efforts to lead these programs. This case study investigated these issues with a sample of elementary school principals (N = 14) working in Texas. Using a modified conceptual lens that categorizes four essential dimensions of instructional leadership for prekindergarten and kindergarten, we found that principals possessed insight into many of these leadership practices but often did not enact these visions due to the academic performance pressures of the upper grades. Furthermore, principals wanted additional support from their district and state administrators to lead their prekindergarten and kindergarten programs better. Such findings illuminate several opportunities to strengthen principals' instructional leadership of prekindergarten and kindergarten.